UiTM Cawangan Pulau Pinang students readiness towards online teaching and learning / Wan Anisha Wan Mohammad, Azlina Mohd Mydin and Rafizah Kechil - Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina; Kechil, Rafizah (Unit Penerbitan JSKM, 2020)
The breakdown of COVID-19 has lead to MCO in Malaysia which started on 18 March 2020. MCO is also known as Movement Control Order. This partial lockdown is implemented to prevent COVID-19 pandemic from being overspread throughout Malaysia. MCO has affected many people around the world especially those in the education field. The closure of school and institute of higher education have given a great impact to the students. To make sure that educations are continuously being distributed to students at their own place during MCO, educators has applied online teaching and learning. Thus, this paper will identify UiTM Cawangan Pulau Pinang students' readiness towards online teaching and learning during MCO based on the survey made before it is being implemented to the students.